Photon beam dose enhancement in AuNP AC tumour through energy moderation of a 6 MeV electron beam: A Monte Carlo study. (March 2022) - van Eeden, D.; Mutsakanyi, S.; du Plessis, F.C.P.
Abstract: Purpose: To use Monte Carlo (MC) simulations (BEAMnrc and DOSXYZnrc) to investigate different moderators to slow down 6 MeV electrons before striking a tungsten bremsstrahlung target. The generated x-ray beam is then used to study the dose-effect when the beam traverses a gold-nanoparticle (AuNP) enriched tumour. Materials and methods: In this study, the 6 MV linear accelerator model was without a beam flattening filter. The BEAMnrc code was used to simulate the 6 MeV electron beam traversing through water or carbon moderators of various thicknesses before striking a thin tungsten target to produce photon beams with effective energies less than the original 6 MV beam (without any moderation). For each beam, a phase-space (PHSP) file was scored to be used in subsequent DOSXYZnrc simulations. The DOSXYZnrc code was utilised to obtain percentage depth dose (PDD) and dose distributions in a 40 × 40 × 40 cm 3 water phantom for each beam. All DOSXYZnrc simulations were repeated but with a tumour model near the surface of the water phantom. Dose enhancement effects (DEFs) were calculated in the tumour model as the ratio of the dose in the tumour with and without gold-nanoparticles (AuNPs) seeded into the tumour at a concentration of 7 mg/g. Results: Water or carbon moderators slowed the primary 6 MeV electron beam down, resulting in lower energy photon beam spectra generated in the tungsten target. Signiﬁcant dependence of DEFs on the mean energy of the resulting x-ray beams was shown as a function of moderator thickness. For beams moderated to kilovolt energies, the effect was more enhanced as anticipated. DEF values ranged between 1.01 and 1.075 for various moderator/bremsstrahlung x-ray target combinations. The highest DEF (1.075) was obtained for a moderator consisting of either 2.5 cm water or 1.4 cm carbon to slow the 6 MeV electrons down before hitting the tungsten target of 0.07 cm thickness. Conclusions: Carbon and water moderators can effectively slow electrons down before using them to generate low energy bremsstrahlung x-rays to enhance the dose in a tumour seeded with AuNPs. DEF's of up to 1.075 can be obtained whilst using beams of energy lower than 1 MV. Highlights: Simulations investigated water and carbon moderators to slow down electrons. The generated photon beam was used to study the dose enhancement effect. The was obtained when the beam traverses a gold-nanoparticle enriched tumour. This study shows the dose enhancement effects by using this proposed method.